Investigation of TF-binding lectins from dietary sources and SRL on proliferation and cell cycle progression in human colon HT29 and SW620 cells. (19th May 2019) - Belur, Shivakumar; Barkeer, Srikanth; Swamy, Bale M.; Yu, Lu-Gang; Inamdar, Shashikala R.
Abstract: TF antigen binding lectins from dietary sources PNA, ACA, ABL, JAC, and SRL from Sclerotium rolfsii have been reported to induce diverse effects on cancer cell proliferation by different mechanisms. This study aimed to compare effects of these lectins on growth and cell cycle progression in colon cancer HT29 and SW620 cells. As reported SRL, ABL, and JAC inhibited while PNA and ACA increased cell proliferation. ABL and JAC treated HT29 cells showed increased cell population in G0/G1 phase. PNA, ACA, ABL, and JAC increased SW620 cell population in S and decreased in G2/M phase. In contrast, SRL and JAC increased hypodiploid population in both the cells. PNA and ACA reduced whereas SRL and ABL diminished cell cyclin D1 expression. SRL, PNA, and ACA also reduced cellular cyclin D3 level while SRL, ABL, and JAC reduced cyclin E levels. ABL decreased CDK5 levels while SRL and ACA completely abolished CDK5 expression. All the lectins completely abolished cyclin D2 expression. These results not only confirms growth regulatory effects of TF-binding lectins but also indicates different effects of these lectins on cell growth is associated with regulation on expression of cell cycle associated proteins in G1-S phase and on cell cycle progression.